Outfitting your home business for much less - Zooi, Walter. (Amacom, 2000)
Finding the right computer system at the right price. Notebooks and other portables. Not all printers are created equal. Multimedia. Palmtops, PDAs, and gadgets. Networking your computers. Business software. Fax machines, copiers, and more. Office furniture. Office supplies...